2022
DOI: 10.1038/s41380-022-01592-w
|View full text |Cite
|
Sign up to set email alerts
|

Maternal attachment insecurity, maltreatment history, and depressive symptoms are associated with broad DNA methylation signatures in infants

Abstract: The early environment, including maternal characteristics, provides many cues to young organisms that shape their long-term physical and mental health. Identifying the earliest molecular events that precede observable developmental outcomes could help identify children in need of support prior to the onset of physical and mental health difficulties. In this study, we examined whether mothers’ attachment insecurity, maltreatment history, and depressive symptoms were associated with alterations in DNA methylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…This would then represent a starting place for uncovering biological, cognitive, and/or social mechanisms that impart psychological resilience, especially in higher-risk populations. An example would be epigenetic changes induced by maternal characteristics that could contribute to the presence of psychological susceptibility or resilience under more severe stress ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…This would then represent a starting place for uncovering biological, cognitive, and/or social mechanisms that impart psychological resilience, especially in higher-risk populations. An example would be epigenetic changes induced by maternal characteristics that could contribute to the presence of psychological susceptibility or resilience under more severe stress ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…2). Several articles described analyses of more than one exposure, resulting in 16 analyses [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] of maternal depression, 8 analyses [32,35,38,39,44,45,47,48] of maternal depression treatment, and 9 analyses [27,32,33,35,38,41,47,49,50] of maternal anxiety (Table S1). Based on STROBE and ROBINS-I criteria, we found that 13 analyses had a moderate risk of bias and 7 had a severe risk of bias (Tables S2 and S3).…”
Section: Included Studiesmentioning
confidence: 99%
“…During the postnatal period, associations between postpartum stress and depression and child DNA methylation have not been extensively studied despite the established relationship between postpartum maternal mental health and child development. While evidence of an association between postpartum depressive symptoms and numerous differentially methylated gene regions have been identi ed in two studies using next-generation sequencing 44 and the Illumina EPIC array 45 respectively, more EWASs, candidate gene studies, and large-scale meta-analyses have yet to be conducted.…”
Section: Introductionmentioning
confidence: 99%